The Impact of Website Interactivity on Users’ Speed in Finding Information: Evidence from Indonesia’s Top 5 Universities - Setyadi, Agung Teguh; Mufid, Mohammad Robihul; Alia, Putri Ariatna; Fahruddin, Agus; Kriswibowo, Rony (International Journal of Computer and Information System (IJCIS), 2025)
University websites serve as primary sources of information for prospective students and the general public. This study aims to examine the relationship between website interactivity and the efficiency of information retrieval at five of the top ten Indonesian universities according to the QS World University Rankings 2025: ITB, UGM, IPB, ITS, and UI. A total of 30 participants from various universities in Surabaya were asked to complete three types of information search tasks on two different university websites. The time taken to complete each task was recorded using a stopwatch. After completing the tasks, participants completed a questionnaire evaluating their perceptions of the websites' interactivity and ease of use. A Two-Way ANOVA revealed significant effects of university website, task type, and their interaction on task completion time. The findings highlight the crucial role of website structure and interactivity in enhancing users’ efficiency when searching for information. A significant interaction effect was found between website interactivity and task completion time (F = 4.395, p < .05).